OAS: An Advanced Undergraduate Office Automated System for Automate Bank Work Routing - E.R. Mahendra Etampawala; Y.R.Uluwita; Jayasinghe J.M.W.C; Abesekara A.W.A.D.C; Nelum Amarasena; Wellalage, Sasini (International Journal of Engineering and Management Research, 2022)
Office automation systems (OAS) have steadily gained popularity as a result of the information technology industry's fast expansion. The promise of office automation, which is meant to increase productivity in the office setting, has caused organizations in both the public and commercial sectors to grow concerned. This issue becomes quite important due to the rising costs of new and enhanced office automation technologies. As a result, industries like banks have improved their front-end client operations using digital solutions. However, a large number of bank processors still depend on personnel and paper. This level of human processing is expensive, sluggish, and may provide results that are highly inconsistent, have significant mistake rates, and pose security risks. Through this research work, our aim is to consider existing significant opportunities in backoffice automation level increase and develop a pilot OAS to work smart with a higher level of efficiency in the office environment. The proposed solution is enriched with image processing methods to authenticate employees to ensure the security of the banking environment by enabling access control and providing a well-accurate employee attendance handling system through web and mobile app facilities which are enabled by GPS and API call technologies. To maintain on-time accurate customer support service, our study has proposed a smart customer handling facility with the help of an AI chatbot and some IoT device materials